Code-Switching Used by Cinta Laura and Yoshi Sudarso on Puella Podcast: Dulu Mau Jadi Guru, Sekarang Masuk Hollywood (A Sociolinguistic Approach) (PANOPTICON: Journal of English Studies, 2025)
Code-switching, the alternation between languages within conversations, reflects complex linguistic and cultural phenomena. This study examines code-switching in the bilingual podcast "Puella Podcast: Dulu Mau Jadi Guru, Sekarang Masuk Hollywood," featuring Cinta Laura and Yoshi Sudarso, using qualitative method by transcribing the data and Poplack’s theory to identify three types of code-switching: intra-sentential, inter-sentential, and tag-switching. A total of 176 instances of code-switching were identified, with tag-switching (74 instances) being the most frequent, followed by intra-sentential (68 instances) and inter-sentential switching (34 instances). Tag-switching was predominantly used to insert English terms into Indonesian sentences for clarity and cultural resonance. The findings reveal that code-switching serves various functions, including enhancing expressiveness, emphasizing emotions, and conveying cultural nuances, as well as providing precision for concepts lacking direct equivalents in one language. Linguistic proficiency, contextual relevance, and cultural identity were key factors influencing the speakers’ use of code-switching, reflecting their multicultural backgrounds and ability to engage bilingual audiences. This study highlights the role of code-switching as a linguistic tool and a medium for cultural representation, identity expression, and audience connection in digital media, contributing to a deeper understanding of bilingualism in contemporary sociolinguistics